Intended and unintended consequences of antiavoidance rules: Evidence from Uganda - Muhammad Bashir; Usama Jamal; Kyle McNabb; Mazhar Waseem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Aggressive profit shifting by multinational enterprises (MNEs) is a growing concern for domestic resource mobilization in developing economies. This paper evaluates the revenue and welfare consequences of a flagship tax avoidance rule that has been implemented in more than 45 countries to prevent profit shifting by MNEs through the debt channel. Our focus is Uganda, a representative developing country that implemented the rule in 2018. Exploiting administrative data comprising the universe of corporate tax returns, we find that the rule does not significantly increase profits reported by MNEs in Uganda or prevent base erosion by them in Uganda. As an unintended consequence, however, the implementation of the rule leads to a contraction in real economic activity, reducing the turnover, employment, and trade of treated MNEs. We highlight the limited targeting efficiency of the rule, questioning its overall effects on welfare.
Keywords: H25; H26; H32; 330; profit shifting; base erosion; tax avoidance